Speculating on vacancy. Issue 1 (19th July 2021) - Noterman, Elsa
Abstract: Property speculation has long served a role in the settler colonial appropriation of land and the racialised uneven development of contemporary cities. This future‐oriented approach to property acquisition and management is underpinned by notions of vacancy that erase past and present forms of possession and associate racialised spaces with lack and risk. Efforts to define, represent, and manage the speculative value of "vacant" properties through predictive mapping work to colonise the future in ways that erase the present and past. In this paper, I reflect on the role of speculative cartographies of property in both reifying and undermining normative urban property regimes. Specifically, I examine the city of Philadelphia's use of cartographic tools to identify "likely" property vacancy and how they relate to ongoing racialised dispossession. I then turn to consider the potential of speculative (counter) cartographies of property to contribute to new political realities, not just prevailing geographies. To do so, I engage with the work of artists and activists who are using mapmaking grounded in Afrofuturism to reclaim and reimagine the space‐times of properties deemed by city officials and developers to be "empty" or "wasted." I suggest that while speculative cartographies of property facilitate the consolidation of liberal property regimes, they also allow for their disruption by revealing their situatedness and contingency – and by facilitating alternative visions of urban futures. Abstract : Property speculation has long served a role in the settler colonial appropriation of land and the racialised uneven development of contemporary cities. In this paper, I consider the city of Philadelphia's predictive mapping of property vacancy to examine how speculative cartographies of property relate to ongoing racialised dispossession. I then turn to consider the potential of speculative (counter) cartographies of property to contribute to new political realities, not just prevailing geographies.